Estudo das manifestações sintomáticas clínicas da doença de Alzheimer: sua relevância no diagnóstico, no tratamento e implicações subjetivo-sociais - Herrera, Gustavo de Almeida (2014)
This work was performed at the Clinic of Cognitive Neurology, Faculty of Medicine Catanduva (SP), Brazil, and is a study of symptomatic manifestations with clinical relevance for the diagnosis and treatment of Alzheimer's disease (AD) and its implications subjective-social . Were evaluated individuals with the diagnosis of AD, vascular dementia (VD), frontotemporal dementia (FTD), and dementia with Lewy bodies disseminated (DCL). 867 individuals complaining of some disturbance of cognition were referred to the clinic and undergo an assessment, the data resulted from the analysis of the history obtained from these patients and their caregivers / family, clinical examination and comprehensive neurological and neuropsychological assessment. Patients with a diagnosis of dementia underwent a battery of tests that contained: complete blood count, fasting blood glucose, serum lipids, renal evaluation, heart, liver, lung and thyroid function, serum vitamin B12 and CT or MRI and nuclear magnetic skull. AD was diagnosed in 42.3% of cases, the DV in 15.6%; DFT at 2.8%, and 1.6% in DCL. The severity of dementia was considered mild in 71.4% of cases, moderate in 24.9% and severe in 3.7%. It was important in the diagnosis of AD at the beginning of the clinical, the onset of oblivion to recent events (96.5%) and did not contribute to the difficulty in finding the words (15%), disorientation in time and space (11, 4%), behavioral changes (16.3%), personality change (12%), depression (22.3%), hallucinations (8.5%), abnormal gait (13.9%), disorders Language (13.1%) and recognition disorder (14.2%). All symptoms and signs above were significant in the evolution of the clinical picture, but at this stage virtually all dementia symptoms overlap. In AD, the onset of symptoms was slowly progressive in 98.1%, and also slowly progressive evolution in 89.9%. The obtained Hachinski score was 0 to 4 in 73.6% of cases of AD. In these, the history of hypertension was obtained in 49.9%, of stroke by 0.5% and 31.6% in psychiatric. Urge the professional care giving for the elderly prepare to take account of the implications of subjective-social order, ie, reflect on the nature of the empirical material which comes to hand: eg., Of how that elderly person and family / caregiver often can manifest on a disease, in a non-accurate or not-consistent, can falter or contradict themselves in their answers, health professionals should be discerning enough to seek the proper interpretation to such speeches